Interest rate (in)sensitivity of emerging market corporate debt : economic analysis based on 2002-2015 empirical evidence - Gubareva, Mariya (2016)
Interest rate sensitivity assessment framework based on fixed income yield indexes is developed and applied to two types of emerging market corporate debt: investment grade and high yield exposures. Our research advances beyond the correlation analyses focused on co- movements in yields and/or spreads of risky and risk-free assets. We show that correlation- based analyses of interest rate sensitivity could appear rather inconclusive and, hence, we investigate the bottom line profit and loss of a hypothetical model portfolio of corporates. We consider historical data covering the period 2002 – 2015, which enable us to assess interest rate sensitivity of assets during the development, the apogee, and the aftermath of the global financial crisis. Based on empirical evidence, both for investment and speculative grades securities, we find that the emerging market corporates exhibit two different regimes of sensitivity to interest rate changes. We observe switching from a positive sensitivity under the normal market conditions to a negative one during distressed phases of business cycles. This research sheds light on how financial institutions may approach interest rate risk management, evidencing that even plain vanilla portfolios of emerging market corporates, which on average could appear rather insensitive to the interest rate risk in fact present a binary behavior of their interest rate sensitivities. Our findings allow banks and financial institutions for optimizing economic capital under Basel III regulatory capital rules.